Industrial training report: Perbadanan Perpustakaan Awam Melaka (PERPUSTAM) / Nur Nazlia Mohd Kamaruzzaman - Mohd Kamaruzzaman, Nur Nazlia (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This paper was written to satisfy the requirements of the Industrial Training course, IMC690, which was required of students prior to their completing their Bachelor of Information Science (Hons.) Library Management degree. This report summarizes the completed, unique project, and lesson learned throughout the course of six month of industrial training at the PERBADANAN PERPUSTAKAAN AWAM MELAKA location. Included are PERPUSTAM’s collections and services. Some restrictions and recommendations were made considering the industrial training to assists the organization in enhancing its facilities and services going forward. The paper provides an overview for future students who need to take this course and allows the reader to see what was done throughout the industrial training.